2022
DOI: 10.2196/29303
|View full text |Cite
|
Sign up to set email alerts
|

Direct Access for Patients to Diagnostic Testing and Results Using eHealth: Systematic Review on eHealth and Diagnostics

Abstract: Background The number of people with chronic diseases and the subsequent pressure on health care is increasing. eHealth technology for diagnostic testing can contribute to more efficient health care and lower workload. Objective This systematic review examines the available methods for direct web-based access for patients to diagnostic testing and results in the absence of a health care professional in primary care. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“… 13 (c) Clinical acceptance: Further studies are required for leading technologies to clinical acceptance. 15 (d) Effectiveness: Stronger primary research on the effectiveness of contact tracing technologies is needed. 27 (e) Confidence: Authors confidence in the effect estimates is limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 (c) Clinical acceptance: Further studies are required for leading technologies to clinical acceptance. 15 (d) Effectiveness: Stronger primary research on the effectiveness of contact tracing technologies is needed. 27 (e) Confidence: Authors confidence in the effect estimates is limited.…”
Section: Resultsmentioning
confidence: 99%
“…More studies needed for (i) the use of these as screening tools (ii) to clearly define the ideal population for the use of these systems (iii) formulation of specific guidance on the management of device-detected disease (iv) evidence for policy making decisions by health departments in the future (v) testing to meet regulatory standards. Supportive of ‘Technology proficiency’ Versluis et al 2022 15 Mainly focused on sexually transmitted infections. Examination of direct web-based access methods for diagnostic testing and results, in situations of non-availability of health care professional in primary care.…”
Section: Methodsmentioning
confidence: 99%
“…With such services, patients can order a diagnostic test online, for example, for COVID-19, perform the test at home or a facility, and view the result online. A recent review [17] showed that most of the included web-based diagnostic services (which were operated independently by health care professionals) were positively evaluated and found very acceptable by patients, but most of the services focused on sexually transmitted infections, and direct access to diagnostic services for other diseases was rare.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first web-based diagnostic service completely integrated into the web-based environment of the GP, and no research has been performed into the type of users and the frequency of use of Homelab. Although services are available where patients can order diagnostic tests themselves without a GP [17], a service where this is integrated in the GP environment is new. Homelab has several advantages for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…An eHealth solution can belong to one of these domains or contain elements from several domains. 3 Research on eHealth has focussed on changed roles for healthcare professionals, [4][5][6] the importance of alignment with care processes, [7][8][9] impact of staff turnover, 10 increased workload 11 and/or decreased workload, [12][13][14] changes in workflow [15][16][17][18] and changes in professional values. 5,7,19 Consequently, previous research shows that eHealth solutions influence the way healthcare professionals conduct their work and provide care.…”
Section: Introductionmentioning
confidence: 99%